2023
DOI: 10.1002/spp2.1511
|View full text |Cite
|
Sign up to set email alerts
|

A new vampyromorph species from the Middle Jurassic La Voulte‐sur‐Rhône Lagerstätte

Abstract: Eight coleoid genera have so far been described from the Callovian‐aged La Voulte‐sur‐Rhône Lagerstätte (c. 165 Ma; Ardèche, France), a locality noted for its unique three‐dimensional preservation of soft tissues. Here, we used high resolution x‐ray‐based imaging methods, in conjunction with reflectance transformation imaging, to study the soft tissues of a previously undescribed coleoid from the La Voulte‐sur‐Rhône locality. This analysis identified both an ink sac and internal light organs, a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The latter is called gladius and consists of a sturdy but flexible chitinous structure within the dorsal mantle. The evolutionary history, anatomy and paleobiology of Mesozoic gladius-bearing coleoids has been extensively studied in the last two decades ( Fischer & Riou, 2002 ; Haas, 2002 ; Košťák, 2002 ; Fuchs, Keupp & Engeser, 2003 ; Fuchs, Engeser & Keupp, 2007a ; Fuchs, Klinghammer & Keupp, 2007b ; Fuchs et al, 2007c ; Fuchs, 2009 ; Fuchs & Iba, 2015 ; Fuchs et al, 2016 ; Bizikov, 2004 ; Bizikov, 2008 ; Fuchs & Weis, 2004 ; Fuchs & Weis, 2008 ; Fuchs & Weis, 2009 ; Fuchs & Weis, 2010 ; Wilby et al, 2004 ; Riccardi, 2005 ; Fuchs, 2006a ; Fuchs, 2006b ; Fuchs, 2006c ; Fuchs, 2007 ; Fuchs, 2009 ; Fuchs, 2015 ; Fuchs, 2016 ; Fuchs, 2019 ; Fuchs, 2020 ; Fuchs & Schultze, 2008 ; Larson, 2010 ; Donovan & Strugnell, 2010 ; Keupp et al, 2010 ; Klug, Schweigert & Dietl, 2010 ; Klug et al, 2015 ; Klug et al, 2021a ; Klug et al, 2021b ; Fuchs & Larson, 2011a ; Fuchs & Larson, 2011b ; Schlögl, Košťák & Hyžny, 2012 ; Breton, Strugnell & Donovan, 2013 ; Donovan & Boletzky, 2014 ; Fuchs & Iba, 2015 ; Jattiot et al, 2015a ; Donovan & Fuchs, 2016 ; Kruta et al, 2016 ; Marroquín, Martindale & Fuchs, 2018 ; Košťák et al, 2021 ; Moreau et al, 2022 ; Rowe et al, 2022 ; Rowe et al, 2023 ) thanks to a few localities with geological horizons particularly favourable to their preservation, the so-called Konservat-Lagerstätten. Thus, studies on exceptionally preserved Mesozoic gladius-bearing coleoids are based on...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is called gladius and consists of a sturdy but flexible chitinous structure within the dorsal mantle. The evolutionary history, anatomy and paleobiology of Mesozoic gladius-bearing coleoids has been extensively studied in the last two decades ( Fischer & Riou, 2002 ; Haas, 2002 ; Košťák, 2002 ; Fuchs, Keupp & Engeser, 2003 ; Fuchs, Engeser & Keupp, 2007a ; Fuchs, Klinghammer & Keupp, 2007b ; Fuchs et al, 2007c ; Fuchs, 2009 ; Fuchs & Iba, 2015 ; Fuchs et al, 2016 ; Bizikov, 2004 ; Bizikov, 2008 ; Fuchs & Weis, 2004 ; Fuchs & Weis, 2008 ; Fuchs & Weis, 2009 ; Fuchs & Weis, 2010 ; Wilby et al, 2004 ; Riccardi, 2005 ; Fuchs, 2006a ; Fuchs, 2006b ; Fuchs, 2006c ; Fuchs, 2007 ; Fuchs, 2009 ; Fuchs, 2015 ; Fuchs, 2016 ; Fuchs, 2019 ; Fuchs, 2020 ; Fuchs & Schultze, 2008 ; Larson, 2010 ; Donovan & Strugnell, 2010 ; Keupp et al, 2010 ; Klug, Schweigert & Dietl, 2010 ; Klug et al, 2015 ; Klug et al, 2021a ; Klug et al, 2021b ; Fuchs & Larson, 2011a ; Fuchs & Larson, 2011b ; Schlögl, Košťák & Hyžny, 2012 ; Breton, Strugnell & Donovan, 2013 ; Donovan & Boletzky, 2014 ; Fuchs & Iba, 2015 ; Jattiot et al, 2015a ; Donovan & Fuchs, 2016 ; Kruta et al, 2016 ; Marroquín, Martindale & Fuchs, 2018 ; Košťák et al, 2021 ; Moreau et al, 2022 ; Rowe et al, 2022 ; Rowe et al, 2023 ) thanks to a few localities with geological horizons particularly favourable to their preservation, the so-called Konservat-Lagerstätten. Thus, studies on exceptionally preserved Mesozoic gladius-bearing coleoids are based on...…”
Section: Introductionmentioning
confidence: 99%
“…, Wilby et al, 2004 ), the Middle Jurassic of La Voulte-sur-Rhône, France ( e.g. , Fischer & Riou, 1982 ; Fischer & Riou, 2002 ; Charbonnier, 2009 ; Kruta et al, 2016 ; Rowe et al, 2022 ; Rowe et al, 2023 ), the Upper Jurassic of Eichstätt, Solnhofen, Painten and Nusplingen Plattenkalks, Germany ( e.g. , Fuchs, 2006b ; Fuchs, 2015 ; Klug, Schweigert & Dietl, 2010 ; Klug et al, 2015 ; Keupp et al, 2010 ), the Upper Jurassic of the Causse Méjean, France ( Moreau et al, 2022 ) and the Upper Cretaceous of Hâkel, Hâdjoula and Sâhel Aalma, Lebanon ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Preservation of nervous systems is known only from fossil localities yielding exceptional preservation. The fossil record of soft tissues is best known among octobrachians (e.g., Clements et al, 2017 ; Fuchs et al, 2010 ; Fuchs, 2006a , 2006b ; Klinghardt, 1932 ; Klug et al, 2015 ; Naef 1922 ; Rowe et al, 2022 , 2023 ). Less is known about the soft tissues of decabrachians (Fuchs et al, 2010 ; Fuchs, 2006a , 2006b ; Klug et al, 2016 , 2019 ), and less still about externally shelled (ectocochleate) cephalopods such as ammonoids and nautiloids (De Baets et al, 2013 ; Klug & Lehmann, 2015 ; Klug et al, 2012 , 2015 , 2021a , 2021c ).…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the soft tissues of decabrachians (Fuchs et al, 2010 ; Fuchs, 2006a , 2006b ; Klug et al, 2016 , 2019 ), and less still about externally shelled (ectocochleate) cephalopods such as ammonoids and nautiloids (De Baets et al, 2013 ; Klug & Lehmann, 2015 ; Klug et al, 2012 , 2015 , 2021a , 2021c ). Some of these reports (Fuchs et al, 2010 , 2021 ; Fuchs, 2006a , 2b ; Klug et al, 2016 , 2020 ; Kruta et al, 2016 ; Rowe et al, 2022 , 2023 ) demonstrated the increased preservational potential for soft tissue anatomy in the coleoid arm crown, which are typically less common than the sclerotized elements such as arm hooks or sucker rings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation